Islamic Law, Adat and State Law Franz von Benda-Beckmann on Systems of Property and Inheritance in Minangkabau - Novelia Musda (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
Franz von Benda-Beckmann is a famous figure in the field of legal pluralism. He is one among scholars who propose to understand the plurality of norms in a society. Among his many works, those on Minangkabau are well-known in the study of Anthropology of Law (Rechtsethnologie). This article attempts to analyse his ideas in a book entitled Property in Social Continuity: Continuity and Change in the Maintenance of Property Relationships through Time in Minangkabau, West Sumatra published in 1979. It has its relevance in the seminar Anthropology of Islamic Law, especially when the book talked about the pluralistic situation of laws in Minangkabau on problems of property and inheritance. Because the book is predominantly about Minangkabau adat, the author focuses on adat’s relation with Islamic law and more specifically on the problem of inheritance which has been a source of much “competition” between both systems to regulate the society. Keyword: Islamic law, adat, Minangkabau, anthropology, legal pluralism